2005
DOI: 10.1161/01.str.0000177886.94134.92
|View full text |Cite
|
Sign up to set email alerts
|

The Linear Behavior of the System Middle Cerebral Artery Flow Velocity and Blood Pressure in Patients With Migraine

Abstract: Background and Purpose-Migraine is considered a disorder of the autonomic nervous system. We used the frequency analysis of dynamic cerebral autoregulation to assess whether blood flow regulation disturbances can be found at the frequencies at which sympathetic and parasympathetic activity is present. Methods-We measured simultaneously mean arterial blood pressure (BP) and the mean blood velocity (V) in the middle cerebral artery using transcranial Doppler ultrasound in 33 healthy controls (mean ageϮSD; 36Ϯ13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…It has previously been reported that dCA is impaired in migraineurs [9], [18]. Müller et al studied 22 migraine patients and 33 healthy controls and found that dCA phase and gain appeared to be completely different in migraineurs compared with healthy controls [9].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has previously been reported that dCA is impaired in migraineurs [9], [18]. Müller et al studied 22 migraine patients and 33 healthy controls and found that dCA phase and gain appeared to be completely different in migraineurs compared with healthy controls [9].…”
Section: Discussionmentioning
confidence: 96%
“…Müller et al studied 22 migraine patients and 33 healthy controls and found that dCA phase and gain appeared to be completely different in migraineurs compared with healthy controls [9]. They suggested that this might be due to the lack of sympathetic and parasympathetic control of CBFV [9].…”
Section: Discussionmentioning
confidence: 99%
“…Muller and Marziniak used frequency analysis of dynamic cerebral autoregulation to assess whether blood flow regulation disturbances may be found at the same frequencies of sympathetic and parasympathetic activity (35), and interpreted the impaired autoregulation observed in migraine patients as a possible lack of sympathetic and parasympathetic control of cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…24 Using spontaneous ABP oscillations in 22 migraine patients (12 with MA), others found clearly pathological phase values in migraine patients in the MCA, both in MO and MA. 25 This led to the assumption of a neurogenic disturbance of the autoregulatory mechanism because of migraine-associated autonomic dysfunction. We could not confirm these results and found phase, gain, and Dx in the MCA to be unchanged between persons with and without migraine.…”
Section: Previous Studies On Migraine and Autoregulationmentioning
confidence: 99%